The Impact of Household Structure and Urban Agglomeration on Real Estate Prices in California - Zhou, Hua (BCP Business & Management, 2022)
The purpose of this paper is to study the impact of regional economic and demographic factors on real estate prices and provide a theoretical basis for policy makers. The first section examines the economic traits of California in the 1990s and reveals a significant urbanization agglomeration impact. Through the use of linear regression, the data analysis model is further developed to examine the reasons for regional variances in home prices. The frequency of numerous families, small family sizes, and the concentration of big cities are proven to have a significant impact on housing costs.